Robustness of the single dressing fraction characterization of polaron structure in multi-mode partial dressing theory - Brown, David W. (2011)
In approaches to polaron theory which attempt to unify small and large polaron behavior, the notion of “partial dressing” plays a central role in determining the allocation of interaction energy between correlations of the small and large polaron types. This paper examines some of the consequences of generalizing from a single dressing fraction to a distribution of dressing fractions. Employing a distribution of dressing fractions allows distinct phonon modes to allocate interaction energy in distinct ratios, thereby supporting a more flexible description of polaron structure than that based on a single dressing fraction applied uniformly to all modes. The distribution of optimal dressing fractions can be characterized by a mean dressing fraction whose properties are in close agreement with the single dressing fraction used previously.